A Study of Job Satisfaction as a Predictor of Organizational Citizenship Behavior - Kaur, Manpreet; Kaur, Surjit; Dhar, Neetu (Prabandhan: Indian Journal of Management, 2015)
The purpose of this study was to analyze the contribution of job satisfaction towards predicting organizational citizenship behavior and its dimensions. This descriptive study was undertaken on a sample of 97 employees working in five ’A’ class hotels in Jammu city. The results revealed that there exists a positive relationship between job satisfaction and all the dimensions of organizational citizenship behavior and the study also found that job satisfaction predicts courtesy and civic virtue more than it predicts the other dimensions of organizational citizenship behavior. These findings will be helpful for hotel management authorities to design different policies to enhance job satisfaction, which in turn will improve citizenship behavior among employees.